An Economic Analysis of the Fiscal Policy Framework in the EMU - Kirill Albrecht (UCL Journal of Law and Jurisprudence, 2015)
This paper intends to provide an economic analysis of the European Monetary Union (EMU). The focus will be on examining the present fiscal policy framework in the EMU. It will be argued that the enforcement of the current framework is weak and has led to excessive deficits in the Eurozone. Measures to strengthen the framework and restore fiscal discipline and sustainable debt levels in the Eurozone will be analysed. It is submitted that the enforcement of the present fiscal framework and fiscal discipline can be strengthened through Eurobonds that are issued jointly by all members of the Eurozone. In order to provide for an effective issuance mechanism a limited form of coordination would be needed that would require minor amendments to existing institutions. Read more